THE ROLE OF ANTONYMS IN SHOWING EMOTIONAL AND THEMATIC CONTRAST IN NORWEGIAN WOOD BY HARUKI MURAKAMI (Eureka Journal of Humanities and Social Research, 2026)
In Norwegian Wood, oppositions such as life and death, memory and forgetting, or hope and despair are not accidental. They shape how we understand the characters’ inner struggles. For example, Toru’s attachment to memory keeps him emotionally tied to the past, while other characters try to survive by forgetting. These contrasts are not just linguistic devices; they reflect the fragile psychological state of youth and the painful movement toward maturity. Rather than functioning as simple word pairs, antonyms become a way for Murakami to express existential tension throughout the novel.
Keywords: Antonymy, semantic contrast, emotional duality, life and death, memory, Murakami.